Crop evapotranspiration dynamics in the Ganges and Mekong deltas - Matheswaran, Karthikeyan; Puvanenthirarajah, Suvasthigha; Jampani, Mahesh; Sena, Dipaka Ranjan (2024)
Asian Mega Deltas (AMD) are food baskets providing livelihoods for farmers and food security for millions. In recent years, many countries have been facing significant pressures to balance sustainable resource use and confront climate change impacts and increasing demands from population growth. In the Ganges and Mekong Deltas, these imminent challenges and anthropogenic pressures are more severe due to increasing pressure to enhance the productive use of land and water resources. The growing variability in water availability is caused by climate change and decreased freshwater flows from upstream. Continuous estimates of evapotranspiration (ET) are essential for evaluating the productivity of agriculture areas in these deltas, but these estimates are often not readily available. In this study, we derived monthly ET in the Ganges and Mekong deltas using remote sensing-based data and an energy balance model to assess its trends. We used the Google Earth Engine (GEE) version of the Surface Energy Balance Algorithm for Land (SEBAL) model with inputs from ERA5 Land meteorological data and LANDSAT 8 and 9 satellite images covering the period from 2014 to 2024. Due to heavy cloud cover during the monsoon season, a gap-filling process was used to produce seamless monthly ET estimates for these two deltas. The ET estimates were aggregated based on land cover types to determine trends in agricultural water use during both the monsoon and non-monsoon seasons. In areas where information about the crop types is available, like in the Mekong Delta, the ET estimates were further aggregated for specific main crop types. Initial results showed an increasing trend in ET at the regional level, indicating intensified agricultural activities within the two assessed deltas. The ET estimates produced from our study will serve as a basis for evaluating the land and water productivity of the deltas, demonstrating the scalability of remote sensing data and energy-based models in estimating ET fluxes at various scales and assessing their trends in different land cover areas.